Umik delnic s pridobitvijo: pravni posel umika, registracija zmanjšanja osnovnega kapitala, varovanje upnikov in izplačila delničarjem - Vončina, Janez (Podjetje in delo, 2014)
The fundamental feature of share capital reduction by withdrawal of own shares, is, as it is visible from the name of this legal institute, withdrawal of shares as a particular corporate law act of the management. It is a legal transaction, which serves as an instrument to cancel the membership rights, while at the same time it is a specific lever for joint-stock company's share capital reduction. Otherwise, the withdrawal of shares is only one of the acts that have to be performed in order to carry out this mode of share capital reduction. Characteristic for this form of reduction are also assembly's resolution passing and registration, registration of share capital reduction, protection of creditors, and payments to the shareholders.
Keywords: Das Kapital; delničarji; delniške družbe; kapital; zmanjšanje